Synody diecezji włocławskiej przed Soborem Trydenckim - Gręźlikowski, Janusz (Prawo Kanoniczne, 2011)
Synodal practice in Włocławek diocese in period before Trident Council has rich and interesting history. Synodal activity since the very beginning had been written into the life, activity and development of Włocławek’s Church and synods played very important ecclesial, legislative and organizational role for that local Church. Thanks to care, efforts and work of synodal legislators – Włocławek’s bishops as well as dispositions and orders included in synodal resolutions, religious, sacramental and disciplinary life was formed of the faithful clerical and secular people as well as organization and structures of diocese. Synodal statutes were basic reference point for the priesthood, administration and Church judicature. In period before Trident Council, calling and holding of at least twenty nine dioecesan and partial synods can be noted in Włocławek’s diocese. This number is probably a lot higher, especially if we are talking about the XIV-th century, but conquests of Teutonic Knights, the wars, annexations and unfavourable political conditions caused that news about synods and their statutes have not lasted till contemporary times. From twenty nine held synods of period before Trident Council, we know the redolutions of only ten of them. Not always are complete synodal statutes, because aften there ore only fragments of resolutions or letters of bishops calling the synod, or other documents presenting synodal orders. In the resolutions of synods held before Trident Council, synodal legislators undertook wide and important range of legislating, administration and judiciary cases, which they wanted to implement into the life of diocese. They were important instruments for Włocławek’s Church of that period, making management of large dioceses easier and more efficient, as well as they allowed bishops to introduce common and provincial law into life his dioceses, adopting in to local conditions. They created also a possibility to deal witch needs, which occurred in the diocese in relation to organization of church structures, religious life of the faithful secular people, task, rights, duties and discipline of priesthood, case connected with performing and taking the sacraments or managing the church prosperity. Their goal was also to watch over the purity of faith, announcing to the priesthood over the purity of faith, announcing to the priesthood the ordinance of The Holy See and resolutions of Provincial Synods as well own orders and instructions from diocese bishop, adjudicate especially complex or important disputes or especially official condemnation of faults or misdemeanours.